Crystal structure analysis and supramolecular association in ethyl N-[amino(iminio)methyl]carbamate dichloride hemi-hydrate - Bamigboye, C; Abbo, H. S.; Kwong, Huey Chong; Tan, Sang Loon *; Tiekink, Edward R. T. *; Kamounah, F. S.; Titinchi, S. J. J. (Oldenbough Verlag, 2021)
X-ray crystallography on [EtOC(=O)N(H)C(=N+H2)NH2]Cl·½H2O (1) shows the asymmetric unit to comprise two independent cations, two chloride anions and crystal water. The main conformational difference between the cations is seen in the relative orientation of the ethyl groups; geometry-optimisation confirms the all-trans conformation is the most stable. The remaining parts of the cations are co-planar and feature intramolecular N–H···O(carbonyl) hydrogen bonds. An analysis of the N–H bonds suggests substantial delocalisation of the positive charge over the CN3 atoms. In the crystal, columns comprising the first independent cation are surrounded by four columns of the second cation within a network of water-O–H···Cl, N–H···Cl and N–H···O(water, carbonyl) hydrogen bonds, many of which are charge-assisted. The packing has been further investigated by Hirshfeld surface analysis, molecular electrostatic potential and interaction energy calculations. The charge-assisted N–H···Cl hydrogen bonds are significantly stronger than the water-O–H···Cl interactions consistent the distribution of the positive charge over the CN3 atoms.